1987
DOI: 10.1084/jem.166.2.461
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of RT6.1+ T lymphocytes induces diabetes in resistant biobreeding/Worcester (BB/W) rats.

Abstract: To investigate the role of RT6+ T cells in the pathogenesis of diabetes in BB/W rats, we treated animals from the diabetes-resistant (DR) subline with anti-RT6.1 lymphocytotoxic mAb. This depleted greater than 95% of peripheral RT6+ T cells but did not substantially reduce levels of circulating T cells or the in vitro response of spleen cells to mitogen. Treatment of 30-d-old DR BB/W rats in this way: induced insulitis and diabetes, rendered nondiabetic RT6-depleted DR rats susceptible to the adoptive transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
1
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(102 citation statements)
references
References 39 publications
6
94
1
1
Order By: Relevance
“…These populations have counter-regulatory properties with respect to autoimmunity, including CsA-AI [11,[31][32][33]36,38,58,59]. In vivo manipulation of the balance between these subsets by depleting antibodies reactive with CD45RC or RT6 as well as adoptive transfer of the respective T cell subpopulations in Diabetic Prone/ BioBreeding (DP/BB) rats has shown that within the RT6 + population a protective population resides, whereas CD45RC + cells aggravate the course of disease [33,38]. Adoptive transfer studies in the model of CsA-AI have shown that adding normal splenocytes or LNC to effector cells derived from diseased rats prevents development of disease [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These populations have counter-regulatory properties with respect to autoimmunity, including CsA-AI [11,[31][32][33]36,38,58,59]. In vivo manipulation of the balance between these subsets by depleting antibodies reactive with CD45RC or RT6 as well as adoptive transfer of the respective T cell subpopulations in Diabetic Prone/ BioBreeding (DP/BB) rats has shown that within the RT6 + population a protective population resides, whereas CD45RC + cells aggravate the course of disease [33,38]. Adoptive transfer studies in the model of CsA-AI have shown that adding normal splenocytes or LNC to effector cells derived from diseased rats prevents development of disease [12].…”
Section: Discussionmentioning
confidence: 99%
“…not lethal) total body x-irradiation results in the development of thyroiditis [62] and diabetes [38] in thymectomized rats and a scala of organ-specific autoimmune phenomena in mice [63]. Furthermore, depletion of RT6 + cells in diabetes-resistant (DR) BB rats leads to the development of diabetes [33]. Moreover, in the mouse CsA has been shown to result in 'forbidden V '-bearing T cells in the thymus and periphery by interference with negative selection [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface Ig* (B) cells were detected with an FITC goat anti-mouse IgG (heavy and light chain specific) . The percent positive cells were determined by flow cytometry as previously described (17) .…”
Section: Methodsmentioning
confidence: 99%